Effects of Silymarin on milk production, liver enzymes, oxidative status and HSP70 gene expression in postparturient Sanjabi ewes - Khamisabadi, Hassan (Cellular and Molecular Biology, 2020)
In the sheep farming industry, breeders need suitable strategies in order to improve milk yields. Meanwhile, silymarin (a natural hepatoprotector substance) has beneficial effects on common oxidative stress at the beginning of lactation. This study was the first research to evaluate the effect of silymarin on milk production, liver enzymes, oxidative and HSP70 responses in the postpartum period. Total 20 Sanjabi ewes were divided into two groups: control (group C: no addition) and treated (group T: received a diet supplemented with silymarin at 2000 mg/kg feed for 15 d after lambing). Data indicated that silymarin reduced postpartum body weight(BW) loss. At the same time, the feed intake (FI) rate increased. In addition, the peaks of milk yields could be achieved earlier compared with control ewes (P< 0.05). Treatment decreased milk compositions (fat and protein) on days 10 and 15. Furthermore, the reactive oxygen species (ROS) and malondialdehyde (MDA) contents in group T were significantly lower than group C (P< 0.05). Also, the activities of endogenous antioxidant enzymes (Glutathione peroxidase, Superoxide dismutase, and Catalase) were increased. Silymarin remarkable increased the serum alanine aminotransferase (ALT) values (P< 0.05). Meanwhile, an increasing trend in the total protein levels was recorded in group T as compared to group C (P> 0.05). The QRT-PCR analysis showed that silymarin supplemental reduced expression of HSP70 gene in blood serum (P< 0.05). It means that changing the diet can affect the activity of heat shock proteins that consequently changes the quality of animal products. In conclusion, our observation relieved that silymarin treatment in the puerperium periodis potentially an effective strategy to improve milk quality via dual hep at oprotective and antioxidant functions.